2004
DOI: 10.1055/s-2004-825602
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(III) Chloride Catalyzed Efficient and Selective Cleavage of Trityl Ethers

Abstract: A highly selective and efficient protocol has been developed for detritylation using 5 mol% BiCl 3 in acetonitrile. The cleavage proceeds at room temperature in high yields and the conditions are mild enough to tolerate a variety of acid-base sensitive functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[18] Both trityl and tert-butyl groups are known to form stable carbocations. Cleavage of the C À O bond with BiCl 3 alone was previously reported for trityl (-CPh 3 ) ethers.…”
Section: Methodsmentioning
confidence: 99%
“…[18] Both trityl and tert-butyl groups are known to form stable carbocations. Cleavage of the C À O bond with BiCl 3 alone was previously reported for trityl (-CPh 3 ) ethers.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the versatile synthetic utility of b-hydroxy-1,3-dioxin-4-ones (for enantioselective versions of the reaction (for a review, see [121]) [150][151][152][153][154]; for other applications [155][156][157][158]), e.g. for the synthesis of 4-hydroxy-2-pyrones via the oxidation of the hydroxyl group [157], there was clearly a need for practical and efficient conditions that involve a bench-stable catalyst, used in very low loading.…”
Section: Bismuth-catalyzed Mukaiyama Aldol Reaction Of Dioxinone-derimentioning
confidence: 99%
“…In general, detritylation is accomplished under strong acidic conditions such as HCOOH, 80% CH 3 COOH, mineral acids, CF 3 COOH, or using Lewis acids such as ZnBr 2 , AlClEt 2 , Yb(OTf) 3 , and Ce(OTf) 4 . BiCl 3 -catalyzed trityl deprotection is a good alternative to these conventional methods as it avoids the use of protic acidic conditions [150]. BiCl 3 -catalyzed trityl deprotection is a good alternative to these conventional methods as it avoids the use of protic acidic conditions [150].…”
Section: Cleavage Of Trityl Ethersmentioning
confidence: 99%
“…We found that the glycosidic bond of 7 was susceptible to cleavage even under mild acidic detritylation condition like using 1% I 2 in methanol at elevated temperature (60 °C). 9 Extensive experimentation disclosed that sabitha's recently developed protocol 10 using bismuth trichloride as a detritylation agent was the method of choice by which the desired product 8 could be obtained cleanly in 65% yield after 48 hours of stirring at room temperature in dry CH 3 CN, albeit with the recovery of some unreacted starting material (Scheme 1). …”
mentioning
confidence: 99%